Artesunate-Induced Vasculitis in an Empirically Treated Patient with Febrile Illness - Ritika Sud; Ridhi Chhabra; Niharika Aggarwal; Lalit Kumar Gupta (Indian Journal of Medical Specialities)
A 55-year-old female presented to the emergency department with maculopapular rashes involving whole body following administration of intravenous artesunate for an acute febrile illness. Leukocytoclastic vasculitis (LCV) was diagnosed with the help of a biopsy, and causes for the condition other than drug induced were investigated and ruled out. Almost 10% of the LCV cases are caused by drugs; however, a literature search did not reveal any documented case of Artesunate-induced vasculitis. We suggest that patients on Artesunate therapy should be monitored for signs and symptoms of LCV.